2017
DOI: 10.1002/csr.1401
|View full text |Cite
|
Sign up to set email alerts
|

Gender Makes a Difference: Investigating Consumer Purchasing Behavior and Attitudes Toward Corporate Social Responsibility Policies

Abstract: The balance between profit maximization and corporate social responsibility (CSR) has become a strategic issue of considerable importance. A key factor in understanding this relationship is identifying consumer reactions to engaging in CSR. Prior literature suggests a gap between consumers' environmental attitudes and behaviors. This study examines this relationship and finds evidence that gender significantly influences this gap between attitudes and behaviors. Specifically, we find that for female segments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 68 publications
5
58
0
3
Order By: Relevance
“…Scholtens & Sievänen (2013) investigate the differences in the socially responsible investing (SRI) in Nordic countries and their study shows that Norway and Sweden, that have more femininity than Finland and Denmark, are both SRI pioneers. Hur et al (2016) and Jones et al (2017) find that female consumers have higher perceptions toward CSR than male consumers. Thanetsunthorn (2015) shows that masculinity has a significantly negative association with CSR performance on employee and community dimensions, but there is no significant relationship with the environmental dimension.…”
Section: Literature Review and Hypothesesmentioning
confidence: 98%
“…Scholtens & Sievänen (2013) investigate the differences in the socially responsible investing (SRI) in Nordic countries and their study shows that Norway and Sweden, that have more femininity than Finland and Denmark, are both SRI pioneers. Hur et al (2016) and Jones et al (2017) find that female consumers have higher perceptions toward CSR than male consumers. Thanetsunthorn (2015) shows that masculinity has a significantly negative association with CSR performance on employee and community dimensions, but there is no significant relationship with the environmental dimension.…”
Section: Literature Review and Hypothesesmentioning
confidence: 98%
“…Further, they revealed the effect on consumer's trust and satisfaction, which are responsible for the creation of long‐term relationships with consumers (Kim, ), as well as for the enhancement of consumer perception and evaluation of companies' brands and products (Dutta & Singh, ). Awareness also mediates the identification process between consumers and companies (also known as consumer–corporate identification), in which the former tends to identify with companies engaged in pro‐social behaviors (Bhattacharya & Sen, ; Jones et al, ; Sen et al, ). This identification process implies the matching of consumers' and companies' values, enabling the creation of consumers' supportive behaviors such as loyalty and positive word of mouth (Bhattacharya & Sen, , ).…”
Section: Conceptual Background and Research Questionsmentioning
confidence: 99%
“…The role of consumers is very relevant, being able to drive changes at both corporate and policy levels, exercising their power in the market by making purchasing decisions. If they identify with companies' values, they are willing to reward them for their social, ethical and environmental commitment (Jones, Reilly, Cox, & Cole, ); by contrast, consumers may boycott companies' products if their expectations and needs are not fully met (Chkanikova & Mont, ; Du, Bhattacharya, & Sen, ; Klein, Smith, & John, ; Lin, Zeng, Wang, Zou, & Ma, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important stakeholders for companies consumers are (Jones, Reilly, Cox, & Cole, 2017), who represent 'a central feature of every CSR report, as they are vital for a corporation's longterm survival' (Öberseder et al, 2013, p. 1842). A growing literature stream has found that consumers take into consideration a company's CSR practices in their evaluation of a firm and in their purchase decisions (Luo & Bhattacharya, 2006;Maignan, 2001;Öberseder et al, 2014;Perera & Chaminda, 2013).…”
Section: Introductionmentioning
confidence: 99%